(untitled) (World Journal of Current Medical and Pharmaceutical Research, 2020)
Sunscreens are those preparation which are rubbed on to the skin surface for the purpose of protection from the harmful UV radiations from the sun. Exposure to those radiations can results in harmful effects such as cancer, edema, varied pigmentation and erythema as a result of DNA damage. Majority of organic chemicals used in sunscreen formulations have not been established as safe. Natural sunscreens gained importance over synthetic ones due to their less side effects, greater protection and easy availability. A wide range of natural products derived from plants, algae and propolis have shown potential photoprotective effect. Natural compounds including flavonoids, cinnamates,polyphenols,carotenoids,anthocyanins,triterpenoid saponins have shown desired Sun Protection Factor (SPF) in addition to anti-inflammatory and anti-oxidant property.